Problems of the geographical information systems in pure research and applied projects - Miklós, László (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
The geographical information systems (GIS) are widely applied in all the landscape ecology, Earth and environmental sciences. The technical development of GIS is very fast and the user sciences are not able to follow this process sufficiently, thus they are even not able to use all the advantages offered by GIS. Several problems concerning the harmonisation of the technical tools and content of GIS are still to be solved. Among those we dealt with the problems as the use of the unified cartographic-topographic basement, of the proper choice of georeferencing elements, of the proper choice of the indices of the elements of the geosystems and their correct georeferencing. All those methodical questions are discussed on the basis of our experiences from the elaboration of landscape-ecological projects, as well as on the basis of results of recently completed project on the GIS of the Ipel’/Ipoly river catchment.
Keywords: GIS; unified cartographic basement; georeferencing; indices